1987
DOI: 10.1007/bf00187258
|View full text |Cite
|
Sign up to set email alerts
|

Further investigation of the stimulus properties of chlordiazepoxide and zolpidem. Agonism and antagonism by two novel benzodiazepines

Abstract: The effects of Ro 16-6028 and Ro 17-1812, two novel benzodiazepines with mixed agonist and antagonist properties, were studied in rats trained to discriminate either chlordiazepoxide or the benzodiazepine receptor ligand zolpidem. In rats discriminating 5 mg/kg chlordiazepoxide from saline both Ro 16-6028 and Ro 17-1812 produced responding on the drug lever. At a dose of 10 mg/kg both compounds gave rise to 100% responding on the lever associated with chlordiazepoxide. The dose-response curve produced by Ro 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…The demonstration of discriminative-stimulus effects of zolpidem in humans is concordant with previous studies that trained rodents to discriminate between zolpidem (1-2 mg/kg) and vehicle (Sanger, 1987;Sanger & Zivkovic, 1986, 1987. The present findings also extend previous human drug-discrimination experiments that established other sedative-hypnotic-anxiolytic compounds (i.e., buspirone, diazepam, pentobarbital, and triazolam) as discriminative stimuli (e.g., Altman, Albert, Milstein, & Greenberg, 1977;Johanson, 1991aJohanson, , 1991bKamien et al, 1994;Oliveto, Bickel, Hughes, Shea, et al, 1992;Rush, Critchfield, Troisi, & Griffiths, 1995;Rush et al, 1997).…”
Section: Discriminative-stimulus Effectssupporting
confidence: 90%
“…The demonstration of discriminative-stimulus effects of zolpidem in humans is concordant with previous studies that trained rodents to discriminate between zolpidem (1-2 mg/kg) and vehicle (Sanger, 1987;Sanger & Zivkovic, 1986, 1987. The present findings also extend previous human drug-discrimination experiments that established other sedative-hypnotic-anxiolytic compounds (i.e., buspirone, diazepam, pentobarbital, and triazolam) as discriminative stimuli (e.g., Altman, Albert, Milstein, & Greenberg, 1977;Johanson, 1991aJohanson, , 1991bKamien et al, 1994;Oliveto, Bickel, Hughes, Shea, et al, 1992;Rush, Critchfield, Troisi, & Griffiths, 1995;Rush et al, 1997).…”
Section: Discriminative-stimulus Effectssupporting
confidence: 90%
“…However, the majority of these studies revealed little or no BZ-appropriate responding engendered by the direct and indirect GABA A agonists, including muscimol, THIP, •y-hydroxybutyrate. and valproate (Ator & Griffiths, 1986, 1989a, 1997Haug, 1983;Nielsen, Valentine, Holohean, Appel, 1983;Rauch & Stolerman, 1986, 1987Spealman, 1985;Woolverton et al, 1999); non-BZ anxiolytics such as buspirone (e.g., Ator & Griffiths, 1986;Hendry, Balster, & Rosecrans, 1983;Rauch & Stolerman, 1987;Sanger et al, 1985;Tang & Franklin, 1991; but see Johanson, 1991b, for effects in humans); various sedative-hypnotic agents, including methaqualone, clomethiazole, chloral hydrate, and triclofos (Ator & Griffiths, 1989a, 1997Evans & Johanson, 1989); anticonvulsants such as phenytoin (Ator & Griffiths, 1997;Rauch & Stolerman, 1987); and muscle relaxants such as methocarbamol (Sannerud, Ator, & Griffiths, 1991b;Sannerud & Ator, 1995a).…”
Section: Full Bz Agonistsmentioning
confidence: 99%
“…These data confirm the results of studies with BZ agonists as discriminative stimuli showing that barbiturates generally share discriminative stimulus effects with BZ agonists. Antagonism studies, however, suggest that these shared effects are mediated by different receptor mechanisms, because the majority of studies demonstrated that the discriminative stimulus effects of barbiturates are not antagonized by the BZ antagonists flumazenil and COS 8216 (Ator & Griffiths, 1983De Vry & Slangen, 1986a;Herling & Shannon, 1982b;Katzman, Herling, & Shannon, 1983;Woolverton & Nader, 1995;Young, Glennon, & Dewey, 1983, 1987.…”
Section: Barbituratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Sanger and Zivkovic 11986a, 19871 and Perrault et al [1988] have suggested that the stimulus properties of chlordiazepoxide and zolpidem may be mediated by different subtypes of benzodiazepine receptors. Support for this hypothesis comes from studies in which specific drugs (Ro 16-6028, Ro 17-1812, CGS 9896, and the B-carbolines: ZK 91296 and B-CMC) antagonized the interoceptive stimulus produced by zolpidem [Sanger, 1987;Sanger andZivkovic, 1986b, 1987;Perrault et al, 19881 but not that produced by chlordiazepoxide. The selective hypnotic activity of zolpidem was further emphasized when it was shown that zolpidem did not increase behavioral output in situations which were sensitive to the stimulant effect of benzodiazepines [Sanger and Zivkovic, 19881, nor did tolerance develop to zolpidem .…”
Section: Introductionmentioning
confidence: 99%